THE ANALYSIS OF TURN SIGNALS IN IELTS SPEAKING PRACTICE (A STUDY OF IELTS EXAMINER AND CANDIDATES IN ELC MAKASSAR) - Sidrah Afriani Rachman (Prodi PGSD FIP UNM, 2016)
This paper concerns turn-taking mechanism and describes especially the kinds of turn signals that speakers interpret with respect to such conversational functions as holding, yielding, taking, claiming, and suppressing the speaking turn. The speakers were examiner and candidates who took turns in IELTS speaking practice. The speaking practices were videotaped and transcribed to allow the analysis of speakers’ turn signals through gesture, verbal and nonverbal cues. The result shows that the examiner and candidates employed turn taking signals 75 times, turn holding signals 40 times, turn yielding signals 40 times, turn claiming signals 5 times, and turn suppressing signals 2 times. These turn signals were used by the examiner and candidates as indications of holding, yielding, taking, claiming and suppressing the speaking turns.Key words: Turn taking, turn yielding, turn claiming, turn suppressing, IELTS Speaking Practice